Research on the Creep and Fatigue Evaluation Method of the Double-Layered Annulus Metal Hydride Bed Combined with Numerical Modeling and ASME Code - Ping Zhao; XiangGuo Zeng; Huayan Chen; Xiuming Zhang (Advances in Materials Science and Engineering)
Applied to a hydrogen absorption-desorption cycle, the hydrogen storage bed will experience higher exchange temperatures and variety of mechanical load. Due to the complex structure of the double-layered annulus metal hydride bed and the importance of thermal stress on the failure of a metal hydride bed, the numerical modeling of its hot spot stress was carefully carried out. Moreover, in this paper, an analysis method considering the limit failure mode condition is proposed to deal with the stress analysis in the process of hydrogen absorption and desorption. According to the proposed analysis method, the maximum stress of thermal-structural coupling in the process of hydrogen absorption occurs at about 1/3 along the diameter direction and at the geometric mutation of the connection between the cooling pipe and the main body of the hydrogen storage bed in the process of hydrogen desorption. Apart from that, the hydrogen storage bed is also subjected to thermal-mechanical fatigue by the iterative process of absorption and desorption, and its operating temperature range is in the thermal creep temperature region. Based on the distribution of the stress and temperature, evaluation hot sites were selected and the ASME-NB and ASME-NH codes were used to evaluate fatigue and fatigue creep, respectively. The evaluation showed that the fatigue damage generated during its service life is small, while the creep damage is relatively large and the total damage generated during the service life of the hydrogen storage bed is within the safe range. Aiming at the structure and complex process of a double-layer hydrogen storage bed, creep and fatigue evaluation methods are proposed, various failure modes of hydrogen storage bed are highlighted, and the relationship between process parameters and life is established.